Ontogeny of digestive enzymes in clown anemonefish larvae, Amphiprion ocellaris (Perciformes: Pomacentridae) - Velasco-Blanco, Gabriela (2023)
Introduction: Clown anemonefish (Amphiprion ocellaris) is the most popular fish species in the marine aquarium trade, however, there is a lack of information on their digestive physiology during larvae ontogeny, valuable information that helps in the design of specific diets, as well as management protocols for the species. Objective: Characterize the early development of digestive enzymes of A. ocellaris during larvae ontogeny. Methods: From hatching until the 38th day after hatching (DAH), the specific activity of acid and alkaline proteases, trypsin, chymotrypsin, leucine aminopeptidase and lipase were analyzed, while acid and alkaline proteases zymograms were performed. Results: At hatching, all measured enzymes activities were detected. Acid proteases increased in activity from hatching until the 38th DAH. Alkaline proteases, trypsin, chymotrypsin, and leucine aminopeptidase showed the same pattern and maximum activity on the 8th DAH, decreasing at the 38th DAH. Lipase activity showed peaks on the 8th and 30th DAH. Acid zymogram showed a single band, appearing on the 8th DAH. A total of eight alkaline proteases were revealed (154.2, 128.1, 104.0, 59.8, 53.5, 41.9, 36.5 and 25.1 KDa), showing seven bands on the 1st DAH and all bands from the 3rd to 8th DAH, decreasing at two bands (41.9 and 25.1 KDa) in the 38th DAH. Conclusion: A. ocellaris shows a functional stomach on the 8th DAH, where the species on the 38th DAH shows digestive enzymatic pattern to omnivore with a tendency to carnivory. Objective: Characterize the early development of digesive enzymes of A. ocellaris during larval ontogeny. Methods: From hatching until the 38th days after hatching (DAH), the specific activity of acid and alkaline proteases, trypsin, chymotrypsin, leucine aminopeptidase and lipase were analysed, while acid and alkaline proteases zymograms were perfomed. Results: At hatching, all measured enzymes activities were detected. Acid proteases increased in activity from hatching until the 38th DAH. Alkaline proteases, trypsin, chymotrypsin and leucine aminopeptidase showed same pattern and maximum activity on the 8th DAH, decreasing at the 38th DAH. Lipase showed activity peaks on the 8th and 30th DAH. Acid zymogram showed a single band, appearing on the 8th DAH. Total of eight alkaline proteases were reveled (154.2, 128.1, 104.0, 59.8, 53.5, 41.9, 36.5 and 25.1 KDa), showing seven bands on the 1st DAH and all band from the 3rd to 8th DAH, decreasing at two bands (41.9 and 25.1 KDa) in the 38th DAH. Conclusion: Therefore, A. ocellaris shows functional stomach on the 8th DAH, where the species on the 38th DAH shows digestive enzymatic pattern to omnivore with a tendency to carnivory.